บทบาทพยาบาลกับการป้องกันแผลที่เท้าผู้ป่วยเบาหวาน - นุ่มพูล จารุณี (Thai Red Cross Nursing Journal, 2011)
แผลที่เท้าในผู้ป่วยเบาหวานเป็นภาวะแทรกซ้อนเรื้อรังจากเบาหวานที่ส่งผลกระทบต่อคุณภาพชีวิตที่เกี่ยวข้องกับสุขภาพโดยรวมของผู้ป่วย การป้องกันการเกิดแผลที่เท้าดีกว่าการรักษาแผลที่เท้าเมื่อเกิดขึ้นแล้ว ในปัจจุบันสถานบริการสุขภาพบางแห่งยังไม่มีบุคลากรที่เชี่ยวชาญด้านการดูแลเท้า พยาบาลที่ดูแลผู้ป่วยเบาหวานจึงควรมีบทบาทในการป้องกันการเกิดแผลที่เท้า โดยต้องเข้าใจถึงกลไกทางพยาธิสรีรวิทยา ปัจจัยเสี่ยงต่างๆต่อการเกิดแผลที่เท้าในผู้ป่วยเบาหวาน และแนวทางการป้องกันการเกิดแผลที่เท้าในผู้ป่วยเบาหวาน ประกอบด้วย 1) การตรวจคัดกรองเท้า 2) การจำแนกระดับความเสี่ยงต่อการเกิดแผลที่เท้า 3)การดูแลตามลักษณะปัญหาของเท้าและการติดตาม 4) การให้ความรู้ในการดูแลเท้า ดังนั้นการอบรมการป้องกันแผลที่เท้าเพิ่มเติมจะช่วยให้พยาบาลมีความรู้และทักษะสามารถนำไปประยุกต์ใช้ได้อย่างมีประสิทธิภาพ The Nurse’s Role in Preventing Diabetic Foot Ulcers Diabetic foot ulcers are a significant chronic complication of diabetes mellitus that affect the overall health-related quality of life. Prevention of any potential ulcers is better than curing the disease. Currently, there is no well-qualified health care provider for diabetic foot care. Nurses who deliver care to diabetic patients should therefore play an important role in preventing ulceration. Nurses should understand the pathophysiology and risk factors of this complication, as well as know how to prevent diabetic foot ulceration. The guidelines in preventing diabetic foot ulcers are composed of diabetic foot screening, risk identification, diabetic foot care and follow up, and education on diabetic foot care. Hence, additional education on preventing foot ulcers will enhance a nurse’s knowledge and skills towards providing optimal care to diabetic patients.